2017
DOI: 10.1128/aem.03517-16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Seasonal Hypoxia on Activity and Community Structure of Chemolithoautotrophic Bacteria in a Coastal Sediment

Abstract: Seasonal hypoxia in coastal systems drastically changes the availability of electron acceptors in bottom water, which alters the sedimentary reoxidation of reduced compounds. However, the effect of seasonal hypoxia on the chemolithoautotrophic community that catalyzes these reoxidation reactions is rarely studied. Here, we examine the changes in activity and structure of the sedimentary chemolithoautotrophic bacterial community of a seasonally hypoxic saline basin under oxic (spring) and hypoxic (summer) condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
(106 reference statements)
4
28
2
Order By: Relevance
“…Therefore, the bacterial diversity of sediment cores taken in August was studied using 16S rRNA gene amplicon sequencing. The phylogenetic data for the first cm in both Stations 1 and 3 has been previously reported by Lipsewers et al (2017) and here we report data for depth interval of the first 8 cm. In order to assess only the bacterial reads, chloroplast reads were removed.…”
Section: Bacterial Diversitysupporting
confidence: 66%
See 3 more Smart Citations
“…Therefore, the bacterial diversity of sediment cores taken in August was studied using 16S rRNA gene amplicon sequencing. The phylogenetic data for the first cm in both Stations 1 and 3 has been previously reported by Lipsewers et al (2017) and here we report data for depth interval of the first 8 cm. In order to assess only the bacterial reads, chloroplast reads were removed.…”
Section: Bacterial Diversitysupporting
confidence: 66%
“…The decaying biomass of the summer bloom is thought to contribute to the hypoxia/anoxia in the water column during late summer (Hagens et al, 2015). Recently, the microbial community of the sulfidic sediment has been the topic of several studies (Malkin et al, 2014;Seitaj et al, 2015;Vasquez-Cardenas et al, 2015;Rao et al, 2016;Sulu-Gambari et al, 2016a;2016b;Lipsewers et al, 2016;2017). Desulfobulbaceae filaments capable of electrogenic sulfide oxidation (Malkin et al, 2014;Vasquez-Cardenas et al, 2015) and nitrate-accumulating Beggiatoaceae (Seitaj et al, 2015) have been shown to be present in the Den Osse Basin.…”
Section: Study Site and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed above, the presence of NO 3 − ‐storing organisms can pose a significant issue for the IPT. However the presence of these organisms may be transient, with seasonal studies noting the presence of Beggiatoa mats typically only during warmer months when the overlying water is hypoxic (Jäntti and Hietanen ; Bonaglia et al ; Sulu‐Gambari et al ; Lipsewers et al ). Accordingly, during certain months of the year it may be necessary to carry out additional NO 3 − storage experiments or calculations (e.g., Glud et al ; Song et al ).…”
Section: Discussion and Outlookmentioning
confidence: 99%